Tidsättning och övervakning - Dorand, Robin; Karlsson, Lars (2012)
This thesis project lasted during five weeks at SSAB in Luleå and dealt with two tasks. The first task was to research the best possible way to synchronize network equipment and monitoring platforms at SSAB. The second task was to examine the requirements and arrangements for the monitoring platform SCOM.There are three main protocols used to achieve time synchronization: NTP, SNTP and PTP. The most common techniques to synchronize the time is either through the Internet, GPS, radio communications, or manual time setting. After collecting data from two different time sources (local server with attached GPS receiver, and externally via the Internet), and comparing the results, the equipment was configured.The results showed that the most appropriate solution would be to synchronize the equipment to the local server using the NTP protocol. For future implementations new and more powerful hardware with support for redundancy is proposed.SCOM is a modular monitoring and management platform developed by Microsoft. SCOM uses the SNMP protocol for communication between SCOM and various networking equipment.A survey on SCOM consisting of discussions with staff at SSAB regarding requests and comments on the design was conducted. Based upon the information gathered a design idea was conceived. It was made up of logical network equipment diagrams and geographical maps of the plant areas.These maps and diagrams were then integrated into SCOM to create a system which was easy to navigate and understand. Validerat; 20121006 (anonymous)